Perception of People Living with HIV/AIDS on Social Stigma of HIV/AIDS in Sukoharjo District - Haryanti, Titik; Wartini, Wartini (UI Scholars Hub, 2019)
The stigma of wrong society about HIV / AIDS is one of the obstacles to prevention and control of HIV / AIDS in Sukoharjo District. This study aims to determine the relationship of characteristics, causal factors and duration of HIV / AIDS with the perception of people living with HIV to the stigma of society about HIV / AIDS in Sukoharjo District. The research used is analytical descriptive with cross sectional approach. The population is all people with HIV / AIDS until April 2016 amounted to 256 with a sample of 156 people with sampling technique quota sampling. Bivariate analysis with chi square test and multivariate analysis with linear regression. The results showed that most of the respondents were 30-40 years old (69.2%), male gender (60.9%), secondary education (44.2%), private employment (30.8%), HIV / AIDS (66.7%), HIV / AIDS-related causes of freedom (55.8%) and negative perceptions of community stigma about HIV / AIDS (67.9%). The statistical test shows that there is a relationship between age (p value = 0.001) and last education (p value = 0.015) with the perception of people living with HIV / AIDS on community stigma about HIV / AIDS. Multiple regression test is known that the age and the last education of respondents together influence the perception of people living with HIV to the stigma of society about HIV / AIDS and education have more influence than age respondent. The need to provide true information about HIV / AIDS both to PLWHA and the community so that there is no negative stigma about HIV / AIDS.